Copepods associated with polychaete worms in European seas - Kim, Il-Hoi; Sikorski, Andrey; O’reilly, Myles; Boxshall, Geoff A. (Zootaxa, 2013)
Descriptions are given of 18 species of copepods that live in symbiotic association with polychaete worms in European Seas. Three new genera and six new species of the family Clausiidae Giesbrecht, 1895 are described: Boreoclausia rectan. gen. et n. sp. is described from Galathowenia fragilis (Nilson & Holthe, 1985), Boreoclausia holmesi n. gen. et n. sp.is described from Myriochele danielsseni Hansen, 1879, Sheaderia bifida n. gen. et n. sp. from Euclymene oerstedii (Claparède, 1863), Vivgottoia garwoodi n. gen. et n. sp., was found inside the tail fragment of a terebellid host (probably Phisidia aurea Southward, 1956), Rhodinicola tenuis n. sp. from an unknown host, and R. similis n. sp., from Rhodine gracilor (Tauber, 1879). In addition, four other clausiid species, Clausia lubbockii Claparède, 1863, Mesnilia cluthae (T. and A.Scott, 1896), Rhodinicola gibbosus Bresciani, 1964 and R. rugosum (Giesbrecht, 1895), are redescribed in detail on the basis of newly collected material. The previously-unknown hosts of C. lubbockii were found to be species of the spionid polychaete genus Dipolydora Verrill, 1881. Clausia uniseta Bocquet & Stock, 1960 were recognized as a junior subjective synonym of C. lubbockii, and Mesnilia martinensis Canu, 1898 was recognized as a junior subjective synonym of M. cluthae. The sole species of the monotypic family Anomoclausiidae Gotto, 1964, Anomoclausia indrehusae Gotto, 1964, is redescribed based on new material. The host of A. indrehusae, reported here for the first time, is the spionid Pseudopolydora paucibranchiata (Okuda, 1937). Four new species of the family Nereicolidae Claus, 1875 are described, three belonging to the genus Anomopsyllus Sars, 1921: Anomopsyllus bifurcus n. sp. from Notomastus latericeus M. Sars, 1851, A. geminus n. sp. from Ampharete lindstroemi Malmgren, 1867, and A. hamiltonae n. sp., from Mugga wahrbergi Eliasson, 1955. The fourth new species is Vectoriella gabesensis n. sp., both sexes of which are described from the paraonid Aricidea catherinae Laubier, 1967 collected in the Mediterranean Sea off the coast of Tunisia. Another nereicolid, Sigecheres brittae Bresciani, 1964 is redescribed based on new material collected from the type host Sige fusigera Malmgren, 1865. It is recognized as a junior subjective synonym of Nereicola concinna T. Scott, 1902 and the valid name of this taxon becomes Sigecheres concinna (T. Scott, 1902) new combination. A new species of the family Spiophanicolidae Ho, 1984, Spiophanicola atlanticus n. sp., is described based on European material. Previously European material of Spiophanicola Ho, 1984 has been reported as S. spinulosus Ho, 1984, but based on consistent differences between the Californian S. spinulosus and material from Norway and the British Isles, there is sufficient justification to establish a new species for the European material. Finally one new genus and species is described which cannot be placed, with confidence, in any existing family. This new parasite, Notomasticola frondosus n. gen. et n. sp., is based on material from two hosts, a spionid (Pseudopolydora paucibranchiata) and a capitellid (Notomastus latericeus). It is highly derived and may represent a terminal branch within an existing family. The cluster of families using polychaetes as hosts is in need of revision based on a comprehensive phylogenetic analysis.